2011
DOI: 10.1111/j.1750-3841.2011.02463.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Medium‐Voltage Electrical Stimulation on Postmortem Changes in Fat‐Tailed Sheep

Abstract: Effects of different medium-voltage electrical stimulation (ES) and ageing on postmortem changes in longissimus dorsi muscle of the fat-tailed sheep were studied. Fifteen male animals were divided into 5 equal groups (n= 3) including: T₁ (control, without ES), T₂ (100 V/30 s), T₃ (100 V/60 s), T₄ (150 V/30 s), and T₅ (150 V/60 s) with fixed frequency of 50 Hz. Five minutes after sticking, the carcasses were stimulated in order of the treatments. After normal processing, they were kept at 6 °C for 14 d. ES acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…During storage, a significantly higher storage loss and cooking loss were observed in the ES‐treated group than in the control group ( P < 0.05), which was consistent with the results of Abbasvali et al . (2012), reporting that ES reduced WHC in sheep meat. This might have happened because ES causes a strong contraction of the muscle fibres in the meat (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During storage, a significantly higher storage loss and cooking loss were observed in the ES‐treated group than in the control group ( P < 0.05), which was consistent with the results of Abbasvali et al . (2012), reporting that ES reduced WHC in sheep meat. This might have happened because ES causes a strong contraction of the muscle fibres in the meat (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, ES promotes glycolysis, causing a rapid drop in muscle pH. An increase in protein degradation results in severe protein denaturation, which disrupts the muscle cell structure and exposes more hydrophobic groups (Abbasvali et al., 2012), thus decreasing WHC. The difference in storage and cooking losses between the 0.5 and 1 A treatment groups was significant ( P < 0.05) in the early stages of storage; however, no significant difference was observed between the ES‐treated 0.5 and 1 A groups at 8 days storage time ( P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that electrical stimulation resulted in early activation of calpains, accelerated proteolysis of the muscle proteins and increased muscle tenderness in Longissimus dorsi muscle of fat-tailed sheep ( Abbasvali et al, 2012 ), and Longissimus lumborum muscle of cattle ( Ferguson et al, 2000 ; Li et al, 2012 ) and lamb ( Pouliot et al, 2014 ). However, Kim et al (2013) reported that tenderness and proteolysis of the Longissimus dorsi muscles from calves stimulated by low voltage remained unaffected.…”
Section: Meat Processing Technologies Meat Tenderness and Proteolytic Systemsmentioning
confidence: 99%